ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA BANDAR LAMPUNG - Aminah Aminah; Khairudin Khairudin; Indrayenti Indrayenti (Jurnal Akuntansi dan Keuangan, 2019)
This study aims to analyze the factors that influence the quality of the financial statements of the local government of Bandar Lampung City. Data collection is done by distributing questionnaires to employees related to financial reporting. The test results show that the competence of human resources has no significant effect on the quality of the financial statements of the Bandar Lampung city government while the internal control system and government financial supervision have a significant effect on the quality of the Bandar Lampung City financial report.